Gymnema sylvestre as a Potential Anti-Inflammatory and Anti-Biofilm Agent Against Anaerobic Infections: An In Vitro Study - Miranda, Diego Garcia [UNESP]; Tomé, Fernanda Malagutti [UNESP]; Miguel, Manuela Maria Viana [UNESP]; Liberato, Sabrina Ferreira dos Santos [UNESP]; Marcucci, Maria Cristina [UNESP]; Vigerelli, Hugo; Rodrigues, Flavia Pires; Pacheco-Soares, Cristina; Godoi, Bruno Henrique; Carrouel, Florence; de Oliveira, Luciane Dias [UNESP]; Ramos, Lucas de Paula [UNESP] (MDPI, 2025)
This study evaluates the antimicrobial activity of the glycolic extract of G. sylvestre against anaerobic pathogens, along with its cytotoxicity, genotoxicity, anti-inflammatory activity, antioxidant effects, and phytochemical composition. Phytochemical analysis was conducted using high-performance liquid chromatography and liquid chromatography–mass spectrometry, while the antioxidant effect was assessed through a DPPH assay. Antimicrobial action was tested on planktonic cultures and biofilms of Porphyromonas gingivalis, Porphyromonas endodontalis, Parvimonas micra, and Fusobacterium nucleatum. Cytotoxicity was evaluated using mouse macrophages (RAW 264.7), rat fibroblasts (L929), and human keratinocytes (HaCaT). Anti-inflammatory effects were measured by an immunoenzymatic assay (ELISA) on RAW 264.7 cells. Statistical analysis was performed using a one-way ANOVA and Tukey’s test. Phytochemical analysis revealed the presence of phenolic compounds and flavonoids. The extract demonstrated a reduction of over 95% in biofilms of P. gingivalis, P. micra, and F. nucleatum within 5 min of treatment. Cell viability (HaCaT) remained above 80%. Antioxidant activity showed an EC50 of 353.43 µg/mL, achieving a 50% reduction in free radicals. A significant decrease in TNF-α (a pro-inflammatory cytokine) and an increase in IL-10 (an anti-inflammatory cytokine) were observed. In conclusion, the extract of G. sylvestre exhibits promising potential as a therapeutic agent for treating anaerobic infections, inflammation, and oxidative stress.
Keywords: anti-inflammatory agents; antimicrobial agents; biofilms; Gram-negative anaerobic cocci